EKSPLORASI HUBUNGAN ANTARA LITERASI NUMERASI DAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DI MADRASAH TSANAWIYAH - Sabilah, Dwi Sartika; Nuh, Muhammad (Universitas Bhinneka PGRI, 2024)
Numeracy literacy and mathematical creative thinking are essential skills for students to tackle learning challenges and solve problems effectively. However, there are gaps in their understanding of these skills. This study aims to examine the relationship between numeracy literacy and mathematical creative thinking among students. A simple regression and correlation analysis was used as the research method. The sample consisted of 33 students randomly selected from a population of 113. Data were gathered through tests on numeracy literacy and mathematical creative thinking skills after a trial phase. Findings reveal a significant relationship between numeracy literacy and mathematical creative thinking, with a correlation coefficient of 0.857. The R-value of 0.857 indicates that 73.50% of the variation in mathematical creativity skills is explained by numeracy literacy. The study identifies four patterns: students with high literacy and creativity excel in analysis, while those with mixed levels show varying strengths and weaknesses in data interpretation and innovation.